A Matching Model of Endogenous Growth and Underground Firms - Gaetano Lisi; Maurizio Pugno (Economics and Econometrics Research Institute (EERI), 2012)
A matching model will explain both unemployment and economic growth by considering the underground sector and human capital. Three problems can thus be simultaneously accounted for: (i) the persistence of the underground sector, (ii) the ambiguous relationships between underground employment and unemployment, and (iii) between growth and unemployment. Key assumptions are that entrepreneurial ability is heterogeneous, skill accumulation determines productivity growth, job-seekers choose whether to invest in education. The conclusions are that the least able entrepreneurs, whose number is endogenous, set up underground firms, employ unskilled labour, and do not contribute to growth. If the monitoring rate is sufficiently low, underground employment alleviates unemployment, but the economy grows at lower rates.
Keywords: E26; J6; J24; L26; 330; Matching models; endogenous growth; underground economy; entrepreneurship; unemployment